The meaning of the library a cultural history - Crawford, Alice 1958- (Princeton University Press, 2015)
From Greek and Roman times to the digital era, the library has remained central to knowledge, scholarship, and the imagination. Generously illustrated, "The Meaning of the Library" examines this key institution of Western culture. Tracing what the library has meant since its beginning, examining how its significance has shifted, and pondering its importance in the twenty-first century, contributors -- including the librarian of the Congress and the former executive director of the HathiTrust -- present a cultural history of the library. Whether relishing an account of the Alexandrian Library or a look at the stylish railway libraries of nineteenth-century England, readers will find a survey of the library through time. Here, too, are the imagined libraries of fiction, poetry, and film, from Scheherazade's stories to "The Name of the Rose" and beyond